2006
DOI: 10.1021/om060380i
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of the Full Catalytic Cycle of the Suzuki−Miyaura Cross-Coupling on a Model System

Abstract: A computational study with the Becke3LYP DFT functional is carried out on the cross-coupling reaction of vinyl bromide H 2 CdCHBr and vinylboronic acid H 2 CdCHB(OH) 2 catalyzed by palladium diphosphine [Pd(PH 3 ) 2 ] in the presence of an excess of base OH -. The full catalytic cycle is computed, starting from the separated reactants and the catalyst and finishing with the cross-coupled product and the regeneration of the catalyst. The different stages in the cycle (oxidative addition, isomerization, transmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
255
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(264 citation statements)
references
References 51 publications
9
255
0
Order By: Relevance
“…Atom abstraction energies for a 3 nm spherical Pd nanoparticles were calculated to be 45 kcal mol Before reaction oxidative addition of aryl iodides and transmetalation to be 20-25 kcal mol -1 . [52][53] The relatively high activation energies for Pd leaching support the consensus that leaching is the rate-determining step. The surface atomic structure influences the stability and leaching susceptibility of Pd atoms and consequently catalytic activity.…”
Section: Methodsmentioning
confidence: 84%
“…Atom abstraction energies for a 3 nm spherical Pd nanoparticles were calculated to be 45 kcal mol Before reaction oxidative addition of aryl iodides and transmetalation to be 20-25 kcal mol -1 . [52][53] The relatively high activation energies for Pd leaching support the consensus that leaching is the rate-determining step. The surface atomic structure influences the stability and leaching susceptibility of Pd atoms and consequently catalytic activity.…”
Section: Methodsmentioning
confidence: 84%
“…These results are consistent with the experimental observation that pyridine is readily dissociated from 24 in solution. Note that entropy changes (DS) in the gas phase are overestimated with respect to those expected in solution, [40] and therefore, the associated DG values always disfavour the association of molecules.…”
mentioning
confidence: 99%
“…The different possibilities of transmetallation reaction that may take place in the second stage of the asymmetric SM reaction were assessed. It has been shown that the transmetallation step in a typical SM coupling reaction does not proceed without the nucleophilic additive, which enhances the electron density at the boron atom through its coordination and formation of boron-ate adduct [20,21,24,65,66]. In an aqueous solution of inorganic bases, the role of this nucleophile may be played by the hydroxyl anion.…”
Section: Transmetallationmentioning
confidence: 99%